2015
DOI: 10.1039/c5ra16474e
|View full text |Cite
|
Sign up to set email alerts
|

Noble metal ions in CeO2and TiO2: synthesis, structure and catalytic properties

Abstract: In past four decades, CeO 2 has been recognized as an attractive material in the area of auto exhaust catalysis because of its unique redox properties. In presence of CeO 2 , catalytic activity of noble metals supported on Al 2 O 3 gets enhanced due to higher dispersion of noble metals in their ionic form. In last several years, we have been exploring an entirely new approach of dispersing noble metal ions on CeO 2 and TiO 2 matrices for redox catalysis. In this article, dispersing of noble metal ions by solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 218 publications
(388 reference statements)
0
42
0
Order By: Relevance
“…[ 123 ] At a structural level, there should be changes in the atomic environment of the parent CeO 2 structure after substitution of metal ions. The substitution of noble metal ions into CeO 2 lattice further augments these properties.…”
Section: Modulation the Defects Or Oxygen Vacancies Of Ceria Nanomatementioning
confidence: 99%
“…[ 123 ] At a structural level, there should be changes in the atomic environment of the parent CeO 2 structure after substitution of metal ions. The substitution of noble metal ions into CeO 2 lattice further augments these properties.…”
Section: Modulation the Defects Or Oxygen Vacancies Of Ceria Nanomatementioning
confidence: 99%
“…It is suggested that noble metal ionic sites and oxide ion vacancies are developed from noble metal‐ion substitution in ceria and titania and behave as adsorption sites for redox catalysis. It was shown that the as‐synthesized noble metal ionic catalysts evaluated to be more active than traditional noble metal nanocatalysts dispersed on oxide supports …”
Section: Oxidation Reactionsmentioning
confidence: 99%
“…Cerium oxide-based materials have been extensively investigated and widely used in various applications, such as oxygen storage, catalysts, gas sensors, UV blockers, electronics and corrosion resistance, and the functional layer is made up of solid oxide fuel cells [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Cerium oxides have been one of the most widely used heterogeneous catalysts for several technologically important reactions [2][3][4][18][19][20]. Their catalytic traits can be attributed to two of their main properties, namely oxygen storage capacity of ceria due to the propensity of Ce to change between Ce 3+ and Ce 4+ and high mobility [21].…”
Section: Introductionmentioning
confidence: 99%
“…It is a very simple and ideal reaction in heterogeneous catalysis and has been used as a model reaction for probing the oxidation activity of several catalysts. CO oxidation has been carried out over different types of CeO 2 -based oxide catalysts [3,4].…”
Section: Introductionmentioning
confidence: 99%